Hydrophobicity and performance analysis of beverage and agricultural waste torrefaction for high-grade bio-circular solid fuel - Napat Kaewtrakulchai; Sutthipoj Wongrerkdee; Benjapon Chalermsinsuwan; Namfon Samsalee; Chao-Wei Huang; Kanit Manatura (Carbon Resources Conversion)
Torrefaction is recognized as a high-performance technology for converting raw biomass into high-grade solid biofuel. In this study, hydrophobic and ANOVA analyses were employed to investigate torrefied brewery waste, palm kernel shell, and water hyacinth residue. Herein, the torrefaction experiments were conducted at four temperatures (180, 230, 280, and 330 °C) for a residence time of 30 min. The biomass type and temperature were crucial in determining the optimum conditions for three response parameters: energy yield (EY), specific energy consumption (SEC), and hygroscopic reduction equilibrium (HRE). Hydrophobicity was assessed by measuring the contact angle (CA), and equilibrium moisture content (EMC) to represent hygroscopic behavior. The ANOVA results indicated that temperature had the most significant impact on the response parameters. Optimal torrefaction of brewery waste at 180 °C yielded an EY of 82.05 %, SEC of 81.88 kWh/kg, and HRE of 23.2 %. These findings highlight the advantages of biomass-derived torrefaction products in waste utilization, transport, and storage of biomass-derived torrefaction products. Furthermore, this study demonstrates an efficient method for enhancing the fuel quality of biomass, contributing significantly to the bio-circular green economy concept.